2011
DOI: 10.1073/pnas.1013676108
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of human Orc6 protein reveals a homology with transcription factor TFIIB

Abstract: The Origin Recognition Complex (ORC) is a six-subunit protein important for the initiation of DNA replication in eukaryotic cells. Orc6 is the smallest and the least conserved among ORC subunits. It is required for the DNA replication but also has a function in cytokinesis in metazoan species, however, the mechanisms of Orc6 action in these processes are not clear. Here we report a structure of the middle domain of human Orc6. This domain has an overall fold similar to the corresponding helical domain of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 46 publications
5
71
0
2
Order By: Relevance
“…However, these results do not necessarily mean that the same inhibition occurs in vivo, because the length of probes/competitors used in this study is limited. It has been reported that ORC4 has an affinity to DNA triplex (43) and that ORC6 has a TFIIB-like DNA-binding domain (44). Thus, it may be possible that the entire ORC binds simultaneously to dsDNA and RNA/ssDNA if an appropriate substrate is used.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results do not necessarily mean that the same inhibition occurs in vivo, because the length of probes/competitors used in this study is limited. It has been reported that ORC4 has an affinity to DNA triplex (43) and that ORC6 has a TFIIB-like DNA-binding domain (44). Thus, it may be possible that the entire ORC binds simultaneously to dsDNA and RNA/ssDNA if an appropriate substrate is used.…”
Section: Discussionmentioning
confidence: 99%
“…The ORC6 protein possesses two functional domains. The conservative N-terminal domain is responsible for DNA interaction, and in metazoans shows structural homology with the transcription factor TFIIB [100]. A small variable domain at the C-terminus is responsible for interactions with other proteins, and with ORC3, in particular [20,101,102].…”
Section: Centrosome Duplication and Cytokinesismentioning
confidence: 99%
“…Four ORC subunits (Orc1, -2, -4, and -5) also contain potential wingedhelix domains at their carboxyl termini. The smallest ORC subunit, Orc6, is related to the RNA Pol II auxilliary factor TFIIB in metazoans (Liu et al 2011), although fungal Orc6 lacks this similarity. Like Mcm2 -7 and ORC, Cdc6 is an AAA þ protein in the same initiator clade as the AAA þ ORC subunits, DnaA and DnaC (Iyer et al 2004).…”
Section: Eukaryotic Helicase Loading Proteinsmentioning
confidence: 99%